Butanol effect on consolidated clay. Issue 4 (December 2006) - Sentenac, P.; Taylor, R.N.; Lynch, R.J.; Bolton, M.D.
Abstract : Clay is often used in the liners of landfill repositories to contain waste organic solvents or as a hydraulic barrier against pollutant migration. Some alcohols play a significant role in changing the hydraulic conductivity of clay by inducing the collapse of the clay's pores through desiccation, with water being absorbed by the alcohol. Such desiccation can lead to cracking. Furthermore, gasoline compounds could be more easily transported in the alcohol rich pore fluid. A particular alcohol, Butanol, has been used in centrifuge experiments to attack a simulated consolidated Kaolinite clay layer. The experiments were conducted using a geotechnical centrifuge and a compacted clay model corresponding to an equivalent prototype clay layer that was 2 metres thick according to conventional scaling laws. Pore pressure transducers located in the clay layer monitored changes in suction caused by Butanol attack. The results of the experiments show that the influence of fluids with different surface tension on the air pressure in the clay, is an important factor to consider in addition to the hydraulic pressure and evaporation at every boundary. The results also confirmed the potential cracking effect of Butanol on Clay.